Identification of a novel C33 botryococcane and C33 botryococcanone in the Maoming Basin, China. (October 2018) - Liao, Jing; Lu, Hong; Feng, Qiao; Zhou, Youping; Shi, Quan; Peng, Ping'an; Sheng, Guoying
Highlights: A novel C33 botryococcan-24-one was identified by IR, MS and NMR analyses. A methyl group was found positioned β to the quaternary carbon. A co-occurring C33 botryococcane with the same skeleton as the ketone was also found. A biosynthetic pathway involving cyclobutanation is proposed for both compounds. Abstract: A novel C33 botryococcane in a sedimentary sample from the Maoming Basin in China was found to have a methyl group positioned β to the quaternary carbon C-10 in its structure based on IR, MS and NMR analyses and Lindeman-Adams modelling. This structure is inconsistent with the prediction from the currently accepted botryococcene biosynthetic pathway and different from the skeleton for the C33 botryococcanes suggested in the literature. A C33 botryococcan-24-one with the same carbon skeleton as the C33 botryococcane was also found to co-occur in the sediment sample. The location of the carbonyl group at C-24 is different from that of a previously reported botryococcenone from an Australian collection of race B of Botryococcus braunii where it is positioned at C-15. We propose a biogeochemical pathway to explain the occurrence of this unique skeleton in the Maoming Basin sediment. The biochemical component of the pathway involves electrophilic or nucleophilic attack between two farnesyl diphosphates (FPPs) leading to direct or indirect formation of a C30 botryococcene via a cyclobutane ring intermediate (1′-2-3-2′ cyclisation). A Retro-Prins reaction and subsequent methylation gives rise to C29 and C33 botryococcenes in sequence. The geochemical component involves first in-water-column (photo)-oxidation of the alkene to a C33 botryococcanone and subsequent reduction (hydrogenation) to stabilize the ketone as an alkane.